The effect of radiographic film processing on the radiographic quality in NDT / Azian Murni Ab.Ghani - Ab.Ghani, Azian Murni (2000)
Radiography is one of the NDT methods that is always being used for defects detection in many materials. Since in this method, films are used as permanent information or as a recorded results, hence films have to be processed carefully and effectively. The purpose of this study is to compare the quality of film between manual and automatic film processing and also to prove that the recommended time of film developing through manual processing is the best time to be used. From the results obtained, its show that manual processing is the best technique to be used rather than automatic processing and the time of developing should be maintained as recommended.